2013
DOI: 10.1111/ane.12202
|View full text |Cite
|
Sign up to set email alerts
|

Spasticity in patients with multiple sclerosis - clinical characteristics, treatment and quality of life

Abstract: Spasticity and its symptoms impair personal well-being and quality-of-life. Treatment of spasticity with drugs and physiotherapy is common, but satisfaction with the currently available anti-spastic pharmacotherapy is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 21 publications
3
78
0
5
Order By: Relevance
“…However, many patients fail to respond adequately to these classical medications at tolerable doses or they become resistant to treatment. Burden of disease studies have identified considerable scope to improve further the management and well-being of patients with MS spasticity across Europe [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…However, many patients fail to respond adequately to these classical medications at tolerable doses or they become resistant to treatment. Burden of disease studies have identified considerable scope to improve further the management and well-being of patients with MS spasticity across Europe [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…The epidemiological burden of disease MOVE (MObility ImproVEment) 1 study from Germany reported that MS-related spasticity impaired patients' personal well-being and QoL, and that patients and physicians were largely dissatisfied with pharmacological options for spasticity [1]. Using a protocol similar to that of the German study, MOVE 1 was extended to other European countries; 300 patients were recruited from 32 centers in seven countries: Belgium, Finland, France, Ireland, Norway, Poland and Portugal [2].…”
Section: Ms Spasticity ‘Burden Of Disease' In Europementioning
confidence: 99%
“…Associated symptoms such as spasms, pain and sleep disturbances combine to impact negatively on QoL. Cross-sectional studies from Europe have indicated that advancing severity of MS spasticity correlates directly with worsening QoL [1,3,4]. …”
Section: Impact Of Thc:cbd Oromucosal Spray On Daily Activities and Qmentioning
confidence: 99%
“…Although there is considerable heterogeneity in its clinical expression [5], spasticity is frequently associated with bladder dysfunction, pain and sleep disturbances [3]. In a relevant proportion of patients, spasticity contributes to mobility restrictions and interferes with a wide range of daily activities, increasing the burden of disease for MS patients and their carers [6][7][8]. Worsening spasticity is associated with an increasingly negative impact on health-related quality of life [6,9,10] and higher utilization of healthcare resources [3,10,11].…”
mentioning
confidence: 99%
“…However, good quality evidence regarding their relative efficacy and safety is lacking [13] and many patients with MS spasticity do not respond, do not tolerate or become resistant to their antispasticity medications. Recent burden of disease studies from around Europe reported an overall low level of satisfaction among physicians and patients with available oral pharmacotherapy options for MS spasticity [6,7]. Thus, a need remains for effective options to treat spasticity in MS patients with inadequate symptomatic relief [6,7].…”
mentioning
confidence: 99%